2016
DOI: 10.1039/c5ta10731h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size of La5Ti2CuS5O7on photoelectrochemical properties in solar hydrogen evolution

Abstract: La 5 Ti 2 CuS 5 O 7 (LTC) is an oxysulphide semiconductor with spatially separated one-dimensional carrier transport properties that are applicable to sunlight-driven photoelectrochemical (PEC) water splitting. In this study, rod-like LTC particles with different sizes were prepared by controlling the annealing duration and sequential centrifugation conditions, and their PEC properties were investigated to develop a material design strategy tailored for hydrogen evolution. The larger LTC particles were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…3-8 Recent efforts on the synthesis and characterization of suitable semiconductors led to the development of several material families, including oxynitrides, [9][10] oxysulfides [11][12] and carbonitrides, [12][13][14] for water splitting. Despite the efforts devoted to this research, the maximum photoconversion efficiency obtained experimentally is still far from the ideal one predicted by thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…3-8 Recent efforts on the synthesis and characterization of suitable semiconductors led to the development of several material families, including oxynitrides, [9][10] oxysulfides [11][12] and carbonitrides, [12][13][14] for water splitting. Despite the efforts devoted to this research, the maximum photoconversion efficiency obtained experimentally is still far from the ideal one predicted by thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Most likely, calcination below 1273 K was insufficient to reduce defects in LTCSO samples synthesized by solid‐state reactions. Our previous study suggested that the synthesis of LTCSO under milder conditions induces defects that prevent charge transfer . By contrast, the LTCSO calcined at 1323 K was accompanied by the generation of white impurities, which are thought to have affected the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…This material is applicable to photocatalytic and photoelectrochemical H 2 and O 2 evolution reactions with the aid of sacrificial reagents and an external power source, respectively . The photocurrent generated by a LTCSO photocathode can be improved by increasing the particle size up to several micrometers as a result of decreases in defect densities and the long‐range diffusion of carriers on the order of micrometers . La 5 Ti 2 Cu(S 1‐ x Se x ) 5 O 7 (LTCS 1‐ x Se x O) solid solutions can also be synthesized by solid‐state reactions .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, doped LTC 1− x A x photocathodes have been found to generate photocurrent at a remarkably positive potential of 0.9 V vs. RHE. Therefore, LTC 1− x A x is a promising photocathode material for unassisted sunlight‐driven water splitting based on p/n‐PEC cells …”
Section: Introductionmentioning
confidence: 93%